Translingual Visemes Mapping for Lithuanian Speech Animation - Mazonaviciute, I.; Bausys, R. (Elektronika ir Elektrotechnika, 2011)
Methodology of Lithuanian phonemes visualization using visemes set of the base language appended by new visemes defined to animate specific Lithuanian phonemes is proposed. Translingual visemes mapping for Lithuanian speech animation is applied. Phoneme to viseme mapping module is one of the most important parts of the framework for Lithuanian speech animation. Facial animation engine compatible with MPEG-4 standard is used to integrate data flows. The base language of the exploited engine is English and the proposed architecture explains how it can be driven by Lithuanian phonetics to get samples of animated Lithuanian speech. Translingual phoneme to viseme mapping module offered in this paper is suitable to animate foreign languages. Ill. 2, bibl. 14, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.365